TRANSFORMASI MUTU PEMBELAJARAN MELALUI KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH: STUDI KASUS DI SEKOLAH DASAR - M. Syaifuddin; Sukirman Sukirman; Enung Hasanah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The principal's role as an instructional leader is crucial in accelerating educational standards within the educational unit. This study aims to examine various strategic leadership approaches to optimize the quality of the teaching and learning process, with the research focus being SDN 025 Balikpapan Tengah. The methodology applied in this research is qualitative with a case study design specification. The researcher collected data through a series of techniques, including in-depth dialogue with the principal and teaching staff, direct observation of classroom dynamics, and review of relevant documents. Next, the information obtained was processed through a process of data sorting, presentation of results, and formulation of final conclusions. The results show that improving the quality of learning is carried out through three main strategies. First, strengthening the academic vision that focuses on student learning outcomes. Second, implementing collaborative clinical supervision to support teacher professional development. Third, creating a conducive learning climate through the provision of innovative instructional resources. This study indicates that the shift in the principal's role from administrative manager to instructional leader who is more involved in the pedagogical process is related to increased teacher efficacy and the quality of learning interactions in the classroom. The results of this study strongly indicate the urgency of strengthening principals' managerial capabilities, particularly in the areas of instructional supervision and curriculum governance. This is necessary as a primary foundation for creating a quality and sustainable learning system. ABSTRAK Peran kepala sekolah sebagai pemimpin instruksional merupakan elemen krusial dalam mengakselerasi standar pendidikan di lingkup satuan pendidikan. Studi ini bermaksud untuk membedah berbagai pendekatan strategis kepemimpinan tersebut guna mengoptimalkan kualitas proses belajar-mengajar, dengan lokus penelitian di SDN 025 Balikpapan Tengah. Metodologi yang diterapkan dalam riset ini adalah kualitatif dengan spesifikasi desain studi kasus. Peneliti menghimpun data melalui serangkaian teknik, meliputi dialog mendalam bersama kepala sekolah dan tenaga pendidik, pengamatan langsung terhadap dinamika di kelas, serta penelaahan dokumen relevan. Selanjutnya, informasi yang diperoleh diolah melalui proses pemilahan data, pemaparan hasil, hingga perumusan konklusi akhir. Hasil penelitian menunjukkan bahwa peningkatan mutu pembelajaran dilakukan melalui tiga strategi utama. Pertama, penguatan visi akademik yang berfokus pada capaian belajar siswa. Kedua, pelaksanaan supervisi klinis yang bersifat kolaboratif untuk mendukung pengembangan profesionalisme guru. Ketiga, penciptaan iklim belajar yang kondusif melalui penyediaan sumber daya instruksional yang inovatif. Penelitian ini mengindikasikan bahwa pergeseran peran kepala sekolah dari manajer administratif menjadi pemimpin instruksional yang lebih terlibat dalam proses pedagogis berkaitan dengan peningkatan efikasi guru serta kualitas interaksi pembelajaran di kelas. Hasil studi ini memberikan indikasi kuat mengenai urgensi penguatan kapabilitas manajerial kepala sekolah, khususnya pada aspek pengawasan instruksional dan tata kelola kurikulum. Hal ini diperlukan sebagai fondasi utama dalam menciptakan sistem pembelajaran yang bermutu dan berkelanjutan.